Hepatic Lipid Accumulation and its Impact on Pancreatic β-cell Function in Diet-Induced Diabetic Animal Models - Dsouza, Vinitha; Purushothama, Chethan; Nagalaxmi, Nagalaxmi; Pujari, Gajanand; Samapriya, Neha (Journal of Neonatal Surgery, 2025)
Background: Type 2 diabetes mellitus (T2DM) involves complex interactions between multiple metabolic organs, with emerging evidence suggesting a critical relationship between hepatic lipid accumulation and pancreatic β-cell dysfunction. This study investigated the temporal and mechanistic links between diet-induced hepatic steatosis and subsequent changes in β-cell function using a mouse model of metabolic disease. Method: Male C57BL/6J mice were fed either a control diet or high-fat diet (HFD) for 16 weeks. Comprehensive metabolic phenotyping, including glucose tolerance tests, insulin sensitivity assessments, and detailed lipidomic analyses, was performed at regular intervals. Pancreatic β-cell function was evaluated through glucose-stimulated insulin secretion assays and morphological analyses, while molecular mechanisms were explored using gene expression profiling and protein analysis. Results: HFD feeding induced progressive hepatic lipid accumulation, characterized by a 3.3-fold increase in triglycerides and significant elevations in specific lipid species, particularly ceramides and diacylglycerols. β-cell function showed a biphasic response, with initial compensatory expansion (1.8-fold increase in mass at 8 weeks) followed by significant deterioration by week 16 (39% reduction in mass). This progression coincided with altered expression of key metabolic regulators, including SREBP-1c and PPARγ in the liver, and PDX1 and GLUT2 in pancreatic tissue. Notably, changes in hepatic lipid composition and inflammatory markers preceded the decline in β-cell function, suggesting a causal relationship. Conclusion: These findings establish a temporal sequence linking hepatic lipid accumulation to pancreatic β-cell dysfunction and identify potential therapeutic windows for intervention in T2DM progression. The results highlight the importance of the hepato-pancreatic axis in metabolic disease and suggest that targeting hepatic lipid accumulation might be an effective strategy for preserving β-cell function in T2DM.